Investigation of thermal conductivity and rheological properties of vegetable oil based hybrid nanofluids containing Cu–Zn hybrid nanoparticles. Issue 3 (4th May 2017) - Mechiri, S. K.; Vasu, V.; Venu Gopal, A.
Abstract : Vegetable oils (Ground nut) are being investigated to serve as a possible substitute for non-biodegradable mineral oils, which are currently being used as metal-cutting fluids in machining processes. In this study, thermophysical properties of hybrid nanofluids (vegetable oil) to be used as metalworking cutting fluids are investigated. In-situ synthesis of copper (Cu) and zinc (Zn) combined hybrid particles is performed by mechanical alloying with compositions of 50:50, 75:25, and 25:75 by weight. Characterizations of the synthesized powder were carried out using X-ray diffraction, a particle size analyzer, FE-SEM, and TEM. Hybrid nanofluids with all the three combinations of hybrid nanoparticles were prepared by dispersing them into a base fluid (vegetable oil). The thermophysical properties, such as thermal conductivity and viscosity, were studied for various volume concentrations and at a range of temperatures. Experimental results have shown enhancement in thermal conductivity in all cases and also an increase in viscosity. The enhancement in viscosity is similar in all three combinations, as the particle size and shape are almost identical. The enhancement in thermal conductivity is higher in Cu–Zn (50:50), resulting in better enhancement in thermal conductivity due to the Brownian motion of the particles and higher thermal conductivity of the nanoparticles incorporated.